Pengaruh Model Pembelajaran Flipped Classroom Tipe Traditional Flipped Berbantuan Video Terhadap Kemampuan Berpikir Kreatif Siswa pada Materi Bangun Ruang Sisi Datar - Anis Umi Khoirotunnisa'; Boedy Irhadtanto (IKIP PGRI Bojonegoro, 2020)
Abstract: The purpose of this study was to determine the effect of students' creative thinking abilities using traditional flipped classroom learning models using video-assisted and conventional learning on flat side space. The population in this study were all eighth grade students of MTs Abu Dzarrin. The Samples were taken by cluster random sampling technique. The selected sample is class VIII A as the experimental class and class VIII C as the control class. The instrument used in this study was students' creative thinking abilities instrument in the form of a essay question. The Analysis of the test instrument using the validity test and reliability test. Prerequisite Test analysis uses the normality test and homogeneity test while testing the hypothesis with the t-independence simple test using SPSS 22 for Windows. The average difference test results with the t-test obtained sig 1-tailed by 0,000 with a significance level of 5%. The value of sig <0.05 so that it can be concluded that the creative thinking ability of students is better to use the model of traditional flipped classroom learning assisted video assisted compared to conventional learning Keyword: Flipped Classroom, traditional flipped, creative thinking abilities. Abstrak: Tujuan dari penelitian ini untuk mengetahui pengaruh kemampuan berpikir kreatif siswa dengan menggunakan model pembelajaran flipped classroom tipe traditional flipped berbantuan video dan pembelajaran konvensional pada materi bangun ruang sisi datar. Populasi dalam penelitian ini adalah seluruh siswa kelas VIII MTs Abu Dzarrin. Sampel diambil dengan teknik cluster random sampling. Sampel terpilih yaitu kelas VIII A sebagai kelas eksperimen dan kelas VIII C sebagai kelas kontrol. Instrumen yang digunakan dalam penelitian ini adalah Instrumen kemampuan berpikir kreatif siswa yang berupa soal uraian. Analisis instrumen test menggunakan uji validitas dan uji reliabilitas. Uji Prasarat analisis menggunakan Uji normalitas dan Uji Homogenitas sementara pengujinan hipotesis dengan uji-t independence simple test Menggunakan SPSS 22 for Windows. Hasil uji beda rata-rata dengan uji-t diperoleh sig 1-tailed sebesar 0,000 dengan taraf signifikansi 5%. Nilai sig < 0,05 sehingga dapat disimpulkan bahwa kemampuan berpikir kreatif siswa lebih baik menggunakan model pembelajaran flipped classroom tipe traditional flipped berbantuan video dibandingkan dengan pembelajaran konvensional. Kata kunci: Flipped Classroom, traditional flipped, kemampuan berpikir kreatif.